In situ hybridisation in perspective. - Warford, A (1991)
In the introduction to this review two questions were posed: is the technology associated with ISH ready for general use, and will the method become an important investigative tool? With the exception of the demonstration of some single and low copy sequences, non-radioactive ISH is now sufficiently developed and simplified to make it a routine technique. It is also clear that ISH will continue to have an important research role. In diagnostic pathology the technique is already providing valuable information and the present decade should see the development of many more diagnostic applications.